Metáfora e identidade no reggae em João Pessoa, Cabedelo e Campina Grande. - Mervic, Iztok (2015)
This thesis examines the reggae history in the region of three municipalities of the state of Paraiba, Brasil (João Pessoa, Cabedelo and Campina Grande), while also identifying and describing artists and bands of the present scene. The focus of this thesis is to analyse how the concept of metaphor influences the expression and (re)construction of identity in the reggae practiced in the surveyed area. The survey was conducted on three levels (ethnographical, musicological and technicallinguistic), using techniques of the fieldwork (interviews, observations and informal conversations), musicological analysis, and technical and linguistic analysis of four songs of bands from the surveyed area. The interconnectivity between the linguistic metaphors (analysed by King and Jensen, 1995) and the metaphorical nature of reggae (analysed by Rice, 2003) were observed in this study. The analysis showed that reggae of the great João Pessoa discusses social topics and the field of entertainment, trying to enter into a reality where other musical practices prevail. Since the metaphor affects our thoughts, experiences of reality and the ways in which we act, the importance of metaphorical language in reggae and reggae as a metaphor by itself play an important role in the process of expression and construction of identities in the context of reggae scene in the area of João Pessoa, Cabedelo and Campina Grande.